Masterbatch, resin composition, molded product, and method for producing the same

By pulverizing and grading the metal compound composite and preparing the resin composition, the problems of reducing the washing resistance and poor processability of the antiviral material after washing are solved, and a molded product with excellent antiviral activity and good processability are achieved.

CN115443301BActive Publication Date: 2025-02-11DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180030535.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-10
Filing Date
2021-04-22
Publication Date
2025-02-11
Estimated Expiration
2041-04-22

AI Technical Summary

Technical Problem

The existing antiviral materials have reduced their washing resistance after washing, and the adhesive resin covering causes the antiviral activity to be blocked, and dispersed in the depth direction of the fabric, resulting in the buried active surface, and poor processability.

Method used

By pulverizing and grading the metal compound composite, a master batch is prepared, and a resin composition is diluted with a dilution resin to further make a molded product to ensure that the antiviral active surface is exposed to the surface of the molded body.

Benefits of technology

A molded product with excellent antiviral activity and good processability has been achieved, and the washing resistance and human safety of the molded product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided are: a molded product with excellent antiviral activity and a method for manufacturing the molded product with good processability, as well as a masterbatch, a resin composition, and a method for manufacturing the same. More specifically, the present invention relates to a resin composition, a molded product, and a method for manufacturing the same, wherein the method for manufacturing the resin composition comprises the following steps: a step of preliminarily melt-kneading a thermoplastic resin and a metal compound composite to manufacture a masterbatch; a step of further melt-kneading a thermoplastic resin into the obtained masterbatch, wherein the metal compound composite contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm, and the specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a masterbatch, a resin composition, a molded product, and a method for producing the same. Background Art

[0002] As a function imparted to fiber products (cloth), processing to impart antibacterial properties has been carried out since ancient times. Specifically, silver compounds are usually added or coated. In recent years, not only antibacterial properties, but also antiviral properties (viral inactivation or antiviral activity) are being paid more attention to as a countermeasure against viral infections such as seasonal influenza, new influenza, SARS (severe acute respiratory syndrome), MERS (Middle East respiratory syndrome), and the new coronavirus (COVID-19). Regarding the evaluation method of antiviral properties, JTETC (Fiber Evaluation Technology Agreement) began certification of the antiviral processing mark (SEK mark) in March 2015. After 2015, it is predicted that the Photocatalyst Industry Association, SIAA (Antimicrobial Products Technology Agreement Association), etc. will also formulate certification standards. As a new type of high added value different from the previous antibacterial processing, there is a trend to create products with antiviral properties. As a material with antiviral properties, for example, a material with antiviral activity is known, which contains titanium oxide containing crystalline rutile titanium oxide and a divalent copper compound (hereinafter also referred to as "antiviral material") (see Patent Document 1).

[0003] Such antiviral materials need to be adhered to the fabric using an adhesive (binder) such as an adhesive resin, but a large amount of adhesive resin is required to maintain the antiviral material even after washing the fabric (improve washing resistance). However, if the antiviral material is adhered to the fabric using an adhesive resin, the washing resistance is improved, but there is a problem that the adhesive resin covers the antiviral material, thereby hindering the antiviral activity of the material and failing to exert a sufficient effect.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-155368 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] In addition, various methods have been studied in which the antiviral material is mixed into the fabric raw material itself instead of using such an adhesive resin to adhere to the fabric surface. However, in this case, the antiviral material is dispersed throughout the entire raw material of the fabric, that is, it is dispersed not only in the surface direction of the fibers constituting the fabric but also in the depth direction. Therefore, there are problems such as the active surface being buried and the necessary amount of addition being increased.

[0009] In addition, the inventors of the present invention further discovered during research that when manufacturing the aforementioned antiviral material, secondary aggregation occurs due to the exposure of the active surface, resulting in reduced dispersibility during mixing of the raw material of the fabric, namely the thermoplastic resin. As a result, the antiviral active surface cannot be exposed more on the surface of the molded body, which not only reduces the antiviral activity, but also easily causes yarn breakage and fracture when processing into yarn with a small fineness or into a thin film, which reduces the processability.

[0010] Therefore, the problem to be solved by the present invention is to provide a molded product having excellent antiviral activity and a method for manufacturing the molded product with good processability, which contains the aforementioned antiviral material, i.e., a metal compound complex (hereinafter also referred to as "metal compound complex"), wherein the metal compound complex contains a titanium oxide including a crystalline rutile titanium oxide and a divalent copper compound. In addition, the problem to be solved by the present invention is to provide a masterbatch, a resin composition, and a method for manufacturing the same that can provide such a molded product and a manufacturing method.

[0011] Solutions for solving problems

[0012] The present inventors conducted intensive research to solve the above-mentioned problems and found that by crushing and classifying the aforementioned metal compound composite to remove coarse particles in advance, a masterbatch is prepared, and then the masterbatch is diluted with a diluting resin to prepare a resin composition, which is further prepared into a molded product. Thus, it is possible to provide a molded product with excellent antiviral activity and a method for manufacturing the same, thereby completing the present invention.

[0013] That is, the present invention relates to a method for producing a resin composition, characterized in that it comprises the following steps: step (1), which is to melt-knead a thermoplastic resin (a) and a metal compound composite (b) as essential raw materials in advance to produce a masterbatch; and step (2), which is to further melt-knead a thermoplastic resin (c) into the masterbatch obtained by the aforementioned step (1).

[0014] The metal compound composite (b) contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide.

[0015] The present invention also relates to the method for producing the resin composition, wherein the content of the crystalline rutile-type titanium oxide in the titanium oxide is 50 mol % or more, and the content of the anatase-type titanium oxide is less than 50 mol %.

[0016] The present invention also relates to a method for producing the aforementioned resin composition, wherein the aforementioned crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less in the strongest diffraction peak corresponding to the rutile titanium oxide in an X-ray diffraction spectrum, wherein the X-ray diffraction spectrum is obtained by plotting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays.

[0017] The present invention also relates to a method for producing the resin composition, wherein in the step (1), the metal compound composite (b) is melt-kneaded in an amount within a range of 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a).

[0018] The present invention also relates to the method for producing the resin composition, wherein in the step (2), the thermoplastic resin (c) is melt-kneaded in an amount within a range of 50 to 5,000 parts by mass with respect to 100 parts by mass of the masterbatch.

[0019] The present invention also relates to a method for producing the resin composition, wherein the thermoplastic resin (a) is at least one selected from the group consisting of polyesters, polyamides, polyolefins, thermoplastic elastomers, and silicone resins.

[0020] The present invention also relates to a masterbatch, characterized in that the metal compound composite (b) is contained in an amount within a range of 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a).

[0021] The metal compound composite (b) in the masterbatch contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide.

[0022] The present invention also relates to the masterbatch, wherein the content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more, and the content of the anatase titanium oxide is less than 50 mol %.

[0023] In addition, the present invention relates to the aforementioned masterbatch, wherein the aforementioned crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less in the strongest diffraction peak corresponding to the rutile titanium oxide in an X-ray diffraction spectrum, wherein the X-ray diffraction spectrum is obtained by plotting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays.

[0024] Furthermore, the present invention relates to the masterbatch, wherein the thermoplastic resin (a) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

[0025] The present invention also relates to a resin composition characterized in that it is obtained by melt-kneading the thermoplastic resin (c) into the masterbatch.

[0026] The present invention also relates to a method for producing a resin composition, comprising the step of melt-kneading a thermoplastic resin (c) into the masterbatch.

[0027] Furthermore, the present invention relates to a molded product obtained by molding the above-mentioned resin composition.

[0028] The present invention also relates to a method for producing a molded article, comprising melt-molding the resin composition.

[0029] The present invention also relates to a method for producing a molded article, characterized in that the method comprises the following steps: step (1) of melt-kneading a thermoplastic resin (a) and a metal compound composite (b) as essential raw materials to produce a masterbatch; step (2) of further melt-kneading a thermoplastic resin (c) into the masterbatch obtained in the above step (1); and step (3) of melt-molding the resin composition obtained in the step (2).

[0030] The metal compound composite (b) contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide.

[0031] The present invention also relates to the method for producing the molded article, wherein the content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more, and the content of the anatase titanium oxide is less than 50 mol %.

[0032] In addition, the present invention relates to a method for producing the aforementioned molded article, wherein the aforementioned crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less in the strongest diffraction peak corresponding to the rutile titanium oxide in an X-ray diffraction spectrum, wherein the X-ray diffraction spectrum is obtained by plotting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays.

[0033] The present invention also relates to the method for producing the molded article, wherein in the step (1), the metal compound composite (b) is melt-kneaded in an amount within a range of 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a).

[0034] The present invention also relates to the method for producing the molded article, wherein in the step (2), the thermoplastic resin (c) is melt-kneaded in an amount within a range of 50 to 5,000 parts by mass with respect to 100 parts by mass of the masterbatch.

[0035] The present invention also relates to the method for producing the molded article, wherein the thermoplastic resin (a) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

[0036] The present invention also relates to the method for producing the molded article, wherein the thermoplastic resin (c) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

[0037] The present invention also relates to the method for producing the molded article, wherein the melt molding in the step (3) is a spinning step or a film and / or sheet forming step.

[0038] Effects of the Invention

[0039] According to the present invention, a molded product containing the aforementioned antiviral active material, i.e., a metal compound complex, and having excellent antiviral activity, and a method for manufacturing the molded product with good processability can be provided, wherein the metal compound complex contains a titanium oxide including a crystalline rutile titanium oxide and a divalent copper compound. In addition, according to the present invention, a masterbatch, a resin composition, and a method for manufacturing the same can be provided that can provide such a molded product and a manufacturing method. DETAILED DESCRIPTION

[0040] The masterbatch of the present invention is characterized in that the metal compound composite (b) is contained in an amount of 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a), wherein the metal compound composite (b) in the masterbatch contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm, and the specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide. The masterbatch of the present invention comprises a step (1) of melt-kneading a thermoplastic resin (a) and a metal compound composite (b) as essential raw materials to produce a masterbatch.

[0041] The thermoplastic resin (a) used in the present invention will be described.

[0042] The thermoplastic resin (a) used in the present invention is not particularly limited as long as the effects of the present invention are not impaired. For example, polyester resins, polycarbonate resins, polyamide resins, polyolefin resins, thermoplastic elastomers, silicone resins, rubber-reinforced styrene resins, polyether ketone resins, polyether resins, polyimide resins, polyarylene sulfide resins, polyarylene ether resins, etc. are listed. Among them, polyester resins, polycarbonate resins, polyamide resins, polyolefin resins, thermoplastic elastomers, and silicone resins are preferred.

[0043] As the polyester resin, aromatic polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate are preferably used.

[0044] Examples of the polyamide resin include nylon 6 (also referred to as "polycaprolactam"), nylon 11 (also referred to as "poly(11-aminoundecanoic acid)"), nylon 12 (also referred to as "polylaurolactam" or "poly(12-aminododecanoic acid)"), nylon 6.6 (also referred to as "polyhexamethylene adipamide"), nylon 6.9 (also referred to as "polyhexamethylene azelaic acid or poly(hexamethylene azelaic acid)"), nylon 6.10 (also referred to as "polyhexamethylene sebacamide" or "polyhexamethylene sebacamide"), and polyamides such as nylon 6.10 and nylon 6.10. "Poly (hexamethylene sebacic acid)"), nylon 6.12 (also known as "poly (hexamethylene dodecanediamide)"), nylon 4 (also known as "poly (δ-butyrolactam)"), nylon 7 (also known as "poly (7-aminoheptanoic acid)" or "poly (7-aminooctanoic acid)"), nylon 8 (also known as "poly (8-aminooctanoic acid)" or "poly (8-aminooctanoic acid)"), nylon 10,6 (also known as "poly (decanediamide adipamide"), partially aromatic nylon (PARNS), etc.

[0045] The metal compound complex (b) used in the present invention will be described.

[0046] The metal compound composite (b) used in the present invention contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide.

[0047] The titanium oxide used in the metal compound complex (b) includes crystalline rutile titanium oxide. In the present invention, crystalline rutile titanium oxide refers to a titanium oxide having a half-peak full width of 0.65 degrees or less of the strongest diffraction peak corresponding to rutile titanium oxide in an X-ray diffraction pattern obtained by depicting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays. If the half-peak full width is greater than 0.65 degrees, the crystallinity deteriorates and the antiviral property in the dark is not fully demonstrated. From this viewpoint, the half-peak full width is preferably 0.6 degrees or less, more preferably 0.5 degrees or less, further preferably 0.4 degrees or less, and further preferably 0.35 degrees.

[0048] The content of crystalline rutile titanium oxide in titanium oxide (hereinafter sometimes referred to as "rutile rate") is preferably 50 mol% or more. If the content is 50 mol% or more, there is a tendency for sufficient antiviral activity. From this viewpoint, the rutile rate is preferably 90 mol% or more, and more preferably 94 mol% or more. As described later, the rutile rate is a value measured by XRD.

[0049] From the above viewpoints, the content of anatase titanium oxide in titanium oxide (hereinafter sometimes referred to as "anatase mineralization rate") is preferably less, and the anatase mineralization rate is preferably less than 50 mol%, more preferably less than 10 mol%, further preferably less than 7 mol%, and particularly preferably 0 mol% (i.e., no anatase titanium oxide). The anatase mineralization rate is also a value measured by XRD like the rutile rate.

[0050] The specific surface area of ​​titanium oxide including crystalline rutile titanium oxide is 3 m 2 / g or above. If 3m 2 / g or more, the specific surface area is large, so the frequency of contact with viruses, bacteria and organic compounds becomes greater, and the antiviral and antibacterial properties are excellent. This tendency becomes greater, so it is preferably 5m 2 / g or more, more preferably 8m 2 On the other hand, the upper limit of the specific surface area is not specified, but is preferably 200 m 2 / g or less, more preferably 100m 2 / g or less, more preferably 70m 2 Here, the specific surface area refers to a value related to primary particles measured by the BET method based on nitrogen adsorption.

[0051] Titanium oxide includes titanium oxide produced by gas phase method and titanium oxide produced by liquid phase method, any of which can be used, and titanium oxide produced by gas phase method is more suitable. Gas phase method is a method having a process of obtaining titanium oxide by using titanium tetrachloride as a raw material and reacting with oxygen in gas phase. The titanium oxide obtained by gas phase method has uniform particle size and undergoes a high temperature process during manufacture, so that the crystallinity becomes high. As a result, the antiviral property, organic compound decomposition property and antibacterial property of the obtained photocatalyst in bright and dark places become good.

[0052] On the other hand, the liquid phase method is a method of obtaining titanium oxide by hydrolyzing or neutralizing titanyl sulfate obtained from a liquid in which a raw material ore such as ilmenite is dissolved.

[0053] In more detail, there are two types of liquid phase methods: sulfuric acid method and chlorine method. In the present invention, titanium oxide produced by any production method can be suitably used. Here, the sulfuric acid method has the following steps: using ilmenite ore and titanium slag as raw materials, dissolving them in concentrated sulfuric acid, and separating the iron component in the form of ferric sulfate; hydrolyzing the separated solution to obtain a hydroxide precipitate; calcining the precipitate to take out rutile titanium oxide. In addition, the chlorine method refers to: using synthetic rutile and natural rutile as raw materials, reacting them with chlorine at a high temperature of more than 950°C to synthesize titanium tetrachloride; after undergoing a distillation process as needed, oxidizing it with oxygen to take out rutile titanium oxide.

[0054] It should be noted that as a method for distinguishing titanium oxides produced by the gas phase method and the liquid phase method, analysis of impurities can be cited. Titanium oxides produced by the aforementioned liquid phase method contain zirconium, niobium, etc., which are impurities derived from ilmenite ores and titanium slag, in their products. In contrast, in the gas phase method, since there is a process of refining titanium tetrachloride to remove impurities, these impurities are hardly contained in titanium oxide.

[0055] The metal compound complex (b) used in the present invention contains a divalent copper compound. The divalent copper compound is combined with the aforementioned titanium oxide containing crystalline rutile titanium oxide, thereby not only having excellent antiviral properties, but also fully exhibiting antibacterial properties. In addition, the divalent copper compound has less discoloration caused by oxidation and the like than the monovalent copper compound, so when the divalent copper compound is used, discoloration can be suppressed.

[0056] The divalent copper compound is not particularly limited, and examples thereof include one or two of a divalent copper inorganic compound and a divalent copper organic compound.

[0057] Examples of the divalent copper inorganic compound include divalent copper inorganic acid salts including copper sulfate, copper nitrate, copper iodate, copper perchlorate, copper oxalate, copper tetraborate, copper ammonium sulfate, copper amide sulfate, copper ammonium chloride, copper pyrophosphate, and copper carbonate; divalent copper halides including copper chloride, copper fluoride, and copper bromide; and one or more selected from the group consisting of copper oxide, copper sulfide, blue smithsonite, malachite, and copper azide.

[0058] Examples of the divalent copper organic compound include divalent copper carboxylates. Examples of the divalent copper carboxylate include copper formate, copper acetate, copper propionate, copper butyrate, copper valerate, copper hexanoate, copper heptanoate, copper octanoate, copper nonanoate, copper decanoate, copper myristate, copper palmitate, copper heptadecanoate, copper stearate, copper oleate, copper lactate, copper malate, copper citrate, copper benzoate, copper phthalate, copper isophthalate, copper terephthalate, copper salicylate, copper mellitic acid, copper oxalate, copper malonate, copper succinate, copper glutarate, copper adipate, copper fumarate, copper glycolate, copper glycerate, copper gluconate, copper tartrate, copper acetylacetonate, copper ethylacetoacetate, copper isovalerate, copper β-dihydroxybenzoate, copper diacetoacetate, copper formylsuccinate, copper salicylate, copper bis(2-ethylhexanoate), copper sebacate, and copper naphthenate. Examples of other divalent copper organic compounds include one or more selected from the group consisting of 8-quinolinol copper, copper acetylacetonate, copper ethylacetoacetate, copper trifluoromethanesulfonate, copper phthalocyanine, copper ethoxide, copper isopropoxide, copper methoxide, and copper dimethyldithiocarbamate.

[0059] Among the above-mentioned divalent copper compounds, one or more of copper oxide, divalent copper halides, divalent copper inorganic acid salts and divalent copper carboxylates are preferred, for example, one or more of divalent copper halides, divalent copper inorganic acid salts and divalent copper carboxylates.

[0060] Examples of the divalent copper compound include divalent copper compounds represented by the following general formula (1).

[0061] Cu2(OH)3X (1)

[0062] In the general formula (1), X is an anion, preferably a halogen such as Cl, Br, I; a conjugate base of a carboxylic acid such as CH3COO; NO3, (SO4) 1 / 2 The conjugate base of an inorganic acid such as OH; or

[0063] Among these divalent copper compounds, divalent copper inorganic compounds are more preferred from the viewpoint of less impurities and economical aspect, and copper oxide is further preferred. In addition, the divalent copper compound represented by the above general formula (1) is also preferred. The divalent copper compound may be an anhydride or a hydrate.

[0064] The copper conversion content of the divalent copper compound is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of the aforementioned titanium oxide. If it is 0.01 parts by mass or more, not only the antiviral property is good, but also the antibacterial property is good. In addition, if it is less than 20 parts by mass, the surface of the titanium oxide is prevented from being covered, the antiviral property is well shown, and the antiviral property can be improved with a small amount, which is economical. From this viewpoint, the copper conversion content of the divalent copper compound is more preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and preferably less than 20 parts by mass, more preferably less than 15 parts by mass, and more preferably less than 10 parts by mass.

[0065] Here, the copper-equivalent content of the divalent copper compound relative to 100 parts by mass of the titanium oxide can be calculated from the charged amounts of the raw material of the divalent copper compound and the raw material of the titanium oxide.

[0066] The metal compound composite (b) used in the present invention contains a titanium oxide including a crystalline rutile titanium oxide and a divalent copper compound as essential components as described above, and may contain other optional components within the range that does not impair the purpose of the present invention. Among them, from the viewpoint of improving antiviral activity, the content of the essential component in the metal compound composite (b) is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 99% by mass or more, and particularly preferably 100% by mass.

[0067] In addition, the metal compound composite (b) used in the present invention has excellent dispersibility in the masterbatch, resin composition and molded product. Therefore, as a raw material for manufacturing the masterbatch, the maximum particle size is in the range of less than 45 μm, preferably in the range of less than 20 μm, and more preferably in the range of less than 10 μm.

[0068] By using the metal compound composite (b) having such a maximum particle size as an essential raw material, the masterbatch can be produced with excellent dispersibility, and the masterbatch can be produced in a filtration test (using a single screw extruder with a diameter of 25 mm, at a temperature 20°C or higher than the melting point of the thermoplastic resin (a) component, at 700 cm / s) using a filter having a particle size of preferably 45 μm, more preferably 20 μm, and further preferably 10 μm) 3 / 1 hour speed for melt extrusion), can pass at a ratio of 5MPa / 1kg or less, not only the productivity is excellent, and the resin composition and molded product obtained through this masterbatch also contain the metal compound complex (b) with good dispersibility. As a result, when it is processed into yarn with small fineness or thin film, it is difficult to break the yarn or fracture, which not only improves the processability, but also the antiviral active surface can be exposed to more on the surface of the molded body due to the improved dispersibility of the metal compound complex (b), which can improve the antiviral activity and antibacterial activity.

[0069] The method for producing the metal compound composite (b) used in the present invention is not particularly limited, and examples thereof include the following: <1> and <2> These two methods.

[0070] <1> The metal compound composite (b) used in the present invention can be manufactured by a manufacturing process having a pulverizing process for pulverizing the obtained mixture and a classification process for classifying the pulverized material after a mixing process for mixing a titanium oxide containing a crystalline rutile titanium oxide with a divalent copper compound raw material. In addition, the pulverizing process and the classification process can be performed after a heat treatment process for heat-treating the mixture obtained by the mixing process. In addition, the aforementioned mixture can also be obtained by suspending and adsorbing titanium oxide in an aqueous solution of a copper compound. Specifically, the metal compound composite (b) can be manufactured by the method described in Japanese Patent Gazette No. 5343176.

[0071] In addition, <1> In the above-mentioned crushing step and classification step, the powder can be crushed by using a crusher, etc., so that the average particle size is within the range of 1 [μm] or more and 50 [μm] or less, and then classified by using a sieve. As for the type of sieve, a commonly used standard sieve can be used, and as the size of the mesh, a sieve of 45 [μm] or 25 [μm] can be selected and used according to the maximum particle size.

[0072] <2> The metal compound composite (b) used in the present invention can also be produced through a production process having the following steps: a mixing step of mixing titanium oxide including crystalline rutile titanium oxide, a divalent copper compound or its precursor, water and an alkaline substance; and a separation step of separating the mixed liquid into a solid component and a liquid phase component. Furthermore, if necessary, it can also be produced through a production process having the following steps: a step of washing, pulverizing and classifying the solid component obtained through the separation step; and a step of subsequently heat-treating the solid component from the viewpoint of being able to firmly bond the titanium oxide including crystalline rutile titanium oxide and the divalent copper compound raw material.

[0073] As the precursor of the divalent copper compound, a precursor represented by the following general formula (2) is preferably used.

[0074] CuX2 (2)

[0075] (In formula (2), X represents a halogen atom, CH3COO, NO3 or (SO4) 1 / 2 . )

[0076] As X in the above formula (2), a halogen atom is more preferred, and a chlorine atom is even more preferred.

[0077] exist <1> The amount of the divalent copper compound or its precursor used in the mixing step is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the titanium oxide.

[0078] exist <1> In the mixing step, the water is the solvent in the mixing step, preferably water alone, and other solvents may be included as needed. As the other solvents, alcohol solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, etc.; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, etc.; dimethylformamide, tetrahydrofuran, etc. may be used. These solvents may be used alone or in combination of two or more.

[0079] exist <1> The amount of water used in the mixing step is preferably 1 part by mass or more, more preferably 10 parts by mass or more, and further preferably 100 parts by mass or more, and is preferably 1000 parts by mass or less, and more preferably 500 parts by mass or less, based on 100 parts by mass of the titanium oxide.

[0080] exist <1> In the above, as the alkaline substance, for example, sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, triethylamine, trimethylamine, ammonia, alkaline surfactants and the like can be used, and sodium hydroxide is preferably used.

[0081] From the viewpoint of easy control of the reaction, the aforementioned alkaline substance is preferably added in the form of a solution, and the concentration of the alkaline solution to be added is preferably in the range of 0.1 mol / L or more, more preferably 0.3 mol / L or more, and further preferably 0.5 mol / L or more, and is preferably in the range of 5 mol / L or less, more preferably 4 mol / L or less, and further preferably 3 mol / L or less.

[0082] exist <1> In the mixing step, the titanium oxide, the divalent copper compound or its precursor, water and the alkaline substance are mixed, and the following method can be cited, for example: first, the titanium oxide is mixed in water and stirred as needed, then the divalent copper compound or its precursor is mixed and stirred, and then the alkaline substance is added and stirred. Through this mixing step, the divalent copper compound derived from the divalent copper compound or its precursor is supported on the titanium oxide.

[0083] exist <1> The overall stirring time in the mixing step is not particularly limited, and is preferably 5 minutes or more, more preferably 10 minutes or more, and preferably 120 minutes or less, with 60 minutes or less being a more preferred range. The temperature during the mixing step is not particularly limited, and may be, for example, in the range of room temperature to 70°C or less.

[0084] exist <1> From the viewpoint of favorably supporting the divalent copper compound on the titanium oxide, the pH of the mixture after mixing / stirring the titanium oxide, the divalent copper compound or its precursor, and water and then mixing / stirring the alkaline substance is not particularly limited as long as it is alkaline, but is preferably 8 or more, more preferably 9.0 or more, and preferably 11 or less, more preferably 10.5 or less.

[0085] exist <1> After the mixing step is completed, the mixed solution can be separated as a solid component. Examples of the separation method include filtration, sedimentation separation, centrifugal separation, evaporation and drying, and filtration is preferred. The separated solid component can be washed with water as needed and then mixed with <1> Same crushing, grading, etc.

[0086] exist <2> In the above, it is preferred to heat-treat the solid component from the viewpoint that the divalent copper compound derived from the divalent copper compound or its precursor supported on the titanium oxide can be more firmly bonded after the solid component is obtained. The heat treatment temperature is preferably 150° C. or more, more preferably 250° C. or more, and preferably 600° C. or less, more preferably 450° C. or less. In addition, the heat treatment time is not particularly limited, but is preferably 1 hour or more, more preferably 2 hours or more, and preferably 10 hours or less, more preferably 5 hours or less.

[0087] Through the above <1> or <2> The metal compound composite (b) is obtained by a manufacturing method. As the loading amount of the divalent copper compound supported on the aforementioned titanium oxide, from the viewpoint of antiviral photocatalytic activity, it is preferably in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of the aforementioned titanium oxide. The loading amount of the aforementioned divalent copper compound can be adjusted by the amount of the aforementioned divalent copper compound or its raw material used in the aforementioned mixing step. It should be noted that the method for determining the loading amount of the aforementioned divalent copper compound is described in the examples described below.

[0088] Regarding the composition ratios of the thermoplastic resin (a) and the metal compound complex salt (b) contained in the masterbatch used in the present invention, from the viewpoint of being able to impart excellent dispersibility and antiviral properties to the molded body obtained via the masterbatch, the metal compound complex (b) is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and further preferably 25 parts by mass or more relative to 100 parts by mass of the thermoplastic resin (a). Considering the cost advantages of suppressing blocking and transportation, it is preferably 300 parts by mass or less, more preferably 150 parts by mass or less, and further preferably 100 parts by mass or less.

[0089] In the masterbatch of the present invention, in addition to the components of the thermoplastic resin (a) and the metal compound complex (b), various known additives may be mixed within a range that does not impair the effects of the present invention. Examples of various additives include inorganic flame retardants such as halogen flame retardants, nitrogen flame retardants, phosphate flame retardants, metal hydroxides, oxides, etc.; flame retardants other than organic phosphoric acid metal salts (b) such as silicone flame retardants; antioxidants such as hindered phenol compounds, hydroquinone compounds, phosphite compounds, and their substitution products; weathering agents such as resorcinol compounds, salicylate compounds, benzotriazole compounds, benzophenone compounds, and hindered amine compounds; mold release agents or lubricants such as aliphatic alcohols, aliphatic amides, aliphatic bisamides, diurea compounds, and polyethylene waxes; pigments such as phthalocyanine and carbon black; dyes such as nigrosine and aniline black; talc, Crystallization nucleating agents such as silicon dioxide, kaolin, and clay; plasticizers such as octyl p-hydroxybenzoate and N-butylbenzenesulfonamide; alkyl sulfate type anionic antistatic agents; quaternary ammonium salt type cationic antistatic agents; non-ionic antistatic agents such as polyoxyethylene sorbitan monostearate; antistatic agents such as betaine type amphoteric antistatic agents; various granular, needle-shaped, and plate-shaped fillers such as graphite, barium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, antimony oxide, aluminum oxide, zinc oxide, iron oxide, zinc sulfide, zinc, lead, nickel, aluminum, iron, stainless steel, bentonite, montmorillonite, and synthetic mica; reinforcing materials such as glass fiber, glass flakes, carbon fiber, boron nitride, potassium titanate, and aluminum borate.

[0090] When these additives are added, the amount thereof is not particularly limited as long as the effects of the present invention are not impaired, and the target function can be freely adjusted by adjusting the type and amount of these additives within a range preferably of 0.1 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of the total of the thermoplastic resin (a) and the metal compound composite (b).

[0091] The masterbatch of the present invention can be produced by preliminarily preparing a thermoplastic resin (a) and a metal compound composite (b) as essential raw materials and melt-kneading them.

[0092] In more detail, the antiviral masterbatch of the present invention can be manufactured by a method having a thermoplastic resin (a) and a metal compound complex (b) and performing melt mixing. More specifically, the above-mentioned components are mixed in a manner that the thermoplastic resin (a) and the metal compound complex (b) become a specified mixing amount, and after pre-mixing using a mixer such as a V-type mixer, a ribbon mixer, and a Henschel mixer as needed, a single-screw extrusion mixer, an open roll agitator, a pressurized kneading machine, a Banbury mixer, a twin-screw extrusion mixer, and other known mixers are used, and the resin setting temperature is set to above the melting point for melt mixing. Among them, from the viewpoint of mixing property and productivity, a twin-screw extrusion mixer is preferably used. After melt mixing, it is processed into pellets, etc. according to a conventional method to obtain the masterbatch of the present invention.

[0093] In the method for producing an antiviral masterbatch of the present invention, the metal compound composite (b) may be an aqueous dispersion containing the metal compound composite (b).

[0094] That is, the antiviral masterbatch of the present invention can also be manufactured by a method further comprising the following steps: step (I), pre-mixing a metal compound complex (b), a dispersant and water to prepare an aqueous dispersion containing the above-mentioned metal compound complex (b); step (II), mixing the above-mentioned metal compound complex (b) in the form of the above-mentioned aqueous dispersion with a thermoplastic resin (a), and melt mixing.

[0095] In the aforementioned step (I), as a dispersant, for example, anionic, nonionic, cationic, zwitterionic surfactants can be used. Examples include comb-type structure polymer compounds obtained by adding polyester to polyethyleneimine, or alkylamine derivatives of α-olefin maleic acid polymers. Specifically, Solsperse series (LUBRIZOL), AJISPER series (Ajinomoto), HOMOGENOL series (Kao), etc. can be listed. In addition, BYK series (BYK-Chemie), EFKA series (EFKA), etc. can also be used appropriately. The aqueous dispersion used in the present invention can disperse the aforementioned metal compound complex (b) in water in the presence of such a dispersant.

[0096] In the aforementioned step (I), the amount of the dispersant blended is not particularly limited, but is preferably 1 part by mass or more, more preferably 10 parts by mass or more, and preferably 100% by mass or less, more preferably 50% by mass or less, based on 100 parts by mass of the metal compound composite (b), from the viewpoint of excellent dispersibility.

[0097] In the aforementioned step (I), the amount of water blended is not particularly limited. From the viewpoint of excellent dispersibility, the amount of the metal compound composite (b) may be appropriately adjusted to preferably be 1% by mass or more, more preferably 10% by mass or more, and preferably 80% by mass or less, more preferably 50% by mass or less, relative to the total amount of the metal compound composite (b), the dispersant and water (i.e., the aqueous dispersion).

[0098] In the above step (II), the aqueous dispersion prepared in the step (I) is blended so that the thermoplastic resin (a) and the metal compound composite (b) have predetermined blending amounts, and melt kneading is performed at a resin setting temperature equal to or higher than the melting point of the thermoplastic resin (a).

[0099] For melt mixing, a kneading machine such as an extruder (single-screw extruder or twin-screw extruder), a kneader or a Banbury mixer may be used. Among them, a kneading extruder is preferred from the viewpoint of enabling continuous kneading.

[0100] After the melt-kneading in the above step (II), the mixture is processed into pellets or the like according to a conventional method to obtain the masterbatch of the present invention.

[0101] The resin composition of the present invention can be obtained by adding a thermoplastic resin (c) to the masterbatch in the form of a diluted resin and melt-kneading. By obtaining the resin composition through the masterbatch in this way, the metal compound complex (b) as an antiviral component can be stably and uniformly dispersed, and further, it can also be added at a high concentration, so that an excellent antiviral effect can be imparted to the molded body.

[0102] Here, as the thermoplastic resin (c) used in the present invention, the same resin as the above-mentioned thermoplastic resin (a) can be cited. When the masterbatch containing the thermoplastic resin (a) and the thermoplastic resin (c) are melt-kneaded, the thermoplastic resin (a) and the thermoplastic resin (c) can use the same type of resin or different types of resins according to the purpose. From the viewpoint of compatibility, it is preferred to use the same type of resin.

[0103] In order to manufacture resin composition by masterbatch of the present invention, for example, as long as the aforementioned masterbatch of the present invention and the aforementioned thermoplastic resin (c) for dilution are preferably adjusted in a manner that thermoplastic resin (c) is preferably more than 50 mass parts, more preferably more than 100 mass parts, more preferably more than 500 mass parts and preferably less than 5000 mass parts, more preferably less than 3000 mass parts, and more preferably less than 2000 mass parts relative to 100 mass parts of masterbatch, and melt-mixed. The method of melt-mixed is not particularly limited, and the same method as the manufacture method of the masterbatch can be adopted. The resin composition obtained by melt-mixing is then directly mixed in a molding machine, or the material obtained by temporarily processing into pellets etc. according to a conventional method is mixed in a molding machine, and various known molding methods such as extrusion molding, injection molding, calendering molding, hollow molding, vacuum molding, and pressure molding are used to manufacture resin molded bodies.

[0104] In the resin composition of the present invention, on the basis of the above-mentioned thermoplastic resin (a), the metal compound composite (b) and the thermoplastic resin (c), various known additives can also be mixed within the range that does not impair the effect of the present invention. As various additives, the same additives as those that can be mixed in the above-mentioned masterbatch can be listed.

[0105] The molded product of the present invention has extremely excellent antiviral and antibacterial properties and can be used in applications requiring these activities. Therefore, in addition to being suitably used for applications such as films, sheets, fibers, and tubes, the molded product of the present invention can also be stacked to form a multilayer film and / or multilayer sheet by stacking multiple films and / or sheets, or can be applied to various molded products such as fabrics woven with fibers, and injection molding, compression molding, extrusion molding, drawing molding, blow molding, and transfer molding. Furthermore, a three-dimensional object can also be formed using a hot melt lamination method (FDM: Fused Deposition Molding), a light shaping method (STL: StereoLithography), a powder sintering method (SLS: Selective Laser Sintering), an inkjet method, an inkjet powder lamination method, etc. For example, a forming material using the resin composition of the present invention as a matrix material is melted at a high temperature above the melting temperature of the resin, the melted forming material is extruded and shaped from the nozzle of the head, and multiple layers are stacked to form a three-dimensional object.

[0106] The fabric can be in any form, such as woven fabric, knitted fabric, nonwoven fabric, etc. In addition, the fabric can be colored with disperse dyes, acid dyes, direct dyes, reactive dyes, pigments, etc. as needed. The fabric of the present invention can be used for various fiber products, such as clothing for general use, underwear use, sports use, medical use, etc.; bedding materials such as quilt covers and bed sheets, curtains, carpets, chairs, cushion covers, wallpapers and other interior decoration products; industrial materials such as tent sheets, flags, curtains; raw materials for sheets for transportation vehicles such as automobiles, airplanes, trains, etc.; sanitary materials; fiber materials for air treatment; fiber materials for water treatment, etc.

[0107] In addition, as molded products, they can not only be processed into objects that are easily touched by human hands, such as food packaging containers, bathtubs, door and window partitions, registers, personal computers, smart phones, etc., but can also be used for medical purposes, especially stents, wound embolic bodies, catheters, syringes (needles, shells), shunt tubes, drainage tubes, transplant medical devices, etc.

[0108] The diameter (number average fiber diameter) of the fiber obtained by melt spinning the resin composition of the present invention varies depending on its use, and can be set to any diameter. From the perspective of the smaller the fiber diameter, the better the antiviral activity, it is preferably 100 μm or less, more preferably 40 μm or less, more preferably 20 μm or less, and particularly preferably 10 μm or less. The lower limit is not limited, preferably 0.01 μm or more, more preferably 0.1 μm or more, and more preferably 1 μm or more. Among them, ultrafine fibers such as fibers in the range of 8 μm or less (referred to as microfibers in the present invention) have a tendency to increase the surface area and increase the antiviral activity, so they are particularly preferred. The fiber length is also not limited, and can be a so-called filament (long fiber) with a long fiber length or a so-called staple fiber (staple) with a short fiber length.

[0109] In addition, the thickness of the sheet and / or film obtained by forming the resin composition of the present invention into a sheet and / or film varies depending on its use, and can be set to any thickness, preferably 1 μm or more, more preferably 3 μm or more, and preferably 200 μm or less, more preferably 150 μm or less. The term sheet or film in the present invention is not used to strictly distinguish between sheets and films, but is used to make it clear that any of them are included. As long as they have the characteristics of the present invention, the sheet and film can be interpreted as broadly as possible. As long as the term sheet has the characteristics of the present invention, it is deemed to also include objects called dishes or plates. It should be noted that when it is necessary to distinguish between sheets and films, within the aforementioned range, sheets are usually used when their thickness exceeds about 0.5 mm, and films are usually used when their thickness is up to about 500 μm.

[0110] The metal compound composite (b) used in the present invention is a particle of a metal compound. Even if it is melt-kneaded with the thermoplastic resin (a) and the thermoplastic resin (c), the range of the maximum particle size basically remains unchanged, and the maximum particle size in the resin composition and the molded product manufactured via the masterbatch is the same as above. However, when the maximum particle size exceeds the above range, it is preferred to adjust the melt-kneading conditions such as the shear force and the filter setting so that the maximum particle size falls within the above range.

[0111] Therefore, the maximum particle size of the metal compound complex (b) in the resin composition and the molded article of the present invention can be in the range of less than 45 μm. It is further preferred that: after the resin composition and the molded article are pressed into a film using a microscope specimen, an optical microscope is observed (magnification 200 times) to obtain a particle image, and the particle size (equivalent circle diameter) is measured for at least 1000 particles (even if they are primary particles, they may further include secondary particles) selected at random, the number of particles having a maximum particle size of 20 μm or more of the metal compound complex (b) is in the range of 5 or less, and particularly preferably in the range of 1 or less.

[0112] Regarding the molded article formed by melt-molding the resin composition of the present invention, in particular, the film and / or sheet or fiber formed into a sheet and / or film or fiber, the resin composition and the molded article thereof are produced by once preparing a masterbatch with a metal compound complex (b) having a maximum particle size of less than 45 [μm] and a thermoplastic resin (a), and then further blending a diluent resin. As a result, the metal compound complex (b) as an antiviral active ingredient can be stably dispersed at a high concentration and with good uniformity. As a result, not only excellent antiviral activity and antibacterial activity are exhibited, but also these effects can be maintained for a long time, washing resistance is significantly improved, and human safety, heat resistance, weather resistance and water resistance are also excellent. Furthermore, by removing coarse particles and increasing the specific surface area, effective utilization of particle surface activity and improvement of surface appearance and surface smoothness of the particle molded product are achieved. Furthermore, in the case of a film and / or sheet, damage to the film and / or sheet can be suppressed, and in the case of a fiber, yarn breakage can be suppressed.

[0113] Example

[0114] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.

[0115] (Example 1)

[0116] ·Manufacturing of metal compound complexes

[0117] 6 g (100 parts by mass) of titanium oxide raw material (Showa Denko Ceramics Co., Ltd.; BET specific surface area, rutile rate, anatase rate, brookite rate, half-peak full width and primary particle size are shown in Table 1) were suspended in 100 mL of distilled water, 0.0805 g (0.5 parts by mass in terms of copper conversion) of CuCl2·2H2O (Kanto Chemical Co., Ltd.) was added, and stirred for 10 minutes. A 1 mol / L aqueous solution of sodium hydroxide (Kanto Chemical Co., Ltd.) was added to a pH of 10, and stirring and mixing were performed for 30 minutes to obtain a slurry. The slurry was filtered, and the obtained powder was washed with pure water, dried at 80°C, and pulverized by a horizontal jet mill ("Single Pass Jet Mill" manufactured by Saixin Enterprise Co., Ltd.) with the aid of heated gas. Thereafter, coarse particles larger than 45 μm were removed by a continuous rotary airflow screening device ("Rotary Gas Sieve" manufactured by Saixin Enterprise Co., Ltd.), thereby obtaining a metal compound composite (1) as a composition containing copper and titanium. The BET specific surface area of ​​the obtained metal compound composite (1) was 10 m 2 / g.

[0118] (BET specific surface area)

[0119] The BET specific surface area of ​​the titanium oxide raw material and the metal compound composite was measured using a fully automatic BET specific surface area measuring apparatus "Macsorb, HM model-1208" manufactured by MOUNTECH.

[0120] (Rutile content (rutile conversion rate) and crystallinity (full width at half maximum) in titanium oxide raw material)

[0121] The content (rutilization rate) and crystallinity (full width at half maximum) of the rutile titanium oxide in the titanium oxide raw material were measured by powder X-ray diffraction.

[0122] That is, for the dried titanium oxide raw material, "X'pertPRO" manufactured by PANalytical was used as a measuring device, and a copper target was used. Cu-Kα1 rays were used, and X-ray diffraction measurement was performed under the conditions of tube voltage of 45 kV, tube current of 40 mA, measurement range of 2θ=20~100 deg, sampling width of 0.0167 deg, and scanning speed of 3.3 deg / min. The peak height (Hr) corresponding to rutile crystals, the peak height (Hb) corresponding to brookite crystals, and the peak height (Ha) corresponding to anatase crystals were calculated, and the content of rutile titanium oxide in titanium oxide (rutile rate) was calculated by the following calculation formula. Rutile rate (mol %) = {Hr / (Ha+Hb+Hr)}×100

[0123] In addition, the content of the anatase type titanium oxide (anatase rate) and the content of the brookite type titanium oxide (brookite rate) in the titanium oxide were determined by the following calculation formulas, respectively.

[0124] Anatase mineralization rate (mol%) = {Ha / (Ha+Hb+Hr)}×100

[0125] Brookite mineralization rate (mol%) = {Hb / (Ha+Hb+Hr)}×100

[0126] In the X-ray diffraction pattern obtained by the above X-ray diffraction measurement, the strongest diffraction peak corresponding to the rutile type titanium oxide is selected and the full width at half maximum is measured.

[0127] (Primary particle size)

[0128] The average primary particle size (DBET) (nm) was measured by the BET single point method to determine the specific surface area S (m 2 / g) and calculated by the following formula.

[0129] DBET=6000 / (S×ρ)

[0130] Here, ρ represents the density of titanium oxide (g / cm 3 ).

[0131] Table 1 shows the measurement results of the titanium oxide raw materials used.

[0132] [Table 1]

[0133] <![CDATA[BET specific surface area (m 2 / g)]]> 10 Rutile rate (mol%) 95.9 Anatase mineralization rate (mol%) 4.1 Brookite mineralization rate (mol%) 0.0 Full width at half maximum (degrees) 0.18 Primary particle size (nm) 150

[0134] ·Manufacturing of masterbatch

[0135] 100 parts by mass of polyethylene terephthalate ("MA-2101M" manufactured by UNITIKA Corporation, intrinsic viscosity (IV) of 0.63) and 50 parts by mass of the metal compound composite (1) were mixed and melt-kneaded in a 30 mm φ twin-screw ventilated extruder (set temperature of 280° C., mesh filter with a particle capture diameter of 40 μm). The obtained thermoplastic resin composition was pelletized to obtain a masterbatch (1).

[0136] ·Filament manufacturing

[0137] 10 parts by mass of the masterbatch (1) were mixed with 100 parts by mass of polyethylene terephthalate ("SA-1206" manufactured by UNITIKA, IV: 1.06), and the mixture was vacuum dried at 150°C for 12 hours. Subsequently, the mixture was melt-spun at a spinning temperature of 290°C using a spinning machine, and stretched 3 times to obtain filaments (1) of 144d / 48F.

[0138] ·Manufacturing of knitted fabrics

[0139] The filaments (1) were false-twisted using a false twisting machine, and a 20-gauge knitted fabric (1) was produced using a circular knitting machine.

[0140] (Example 2)

[0141] ·Manufacturing of masterbatch

[0142] A masterbatch (2) was obtained in the same manner as in Example 1 except that the setting temperature when further extruding polyethylene terephthalate into polyamide-6 ("UBE NYLON 1013B" manufactured by Ube Industries, Ltd.) was changed from 280°C to 260°C.

[0143] ·Filament manufacturing

[0144] 10 parts by mass of the masterbatch (2) was mixed with 100 parts by mass of polyamide-6 ("UBE NYLON 1018" manufactured by Ube Industries, Ltd.), and the mixture was vacuum dried at 110°C for 12 hours. Then, the mixture was melt-spun at a spinning temperature of 260°C using a spinning machine, and stretched 3 times to obtain filaments (2) of 144d / 48F.

[0145] ·Manufacturing of knitted fabrics

[0146] A knitted fabric (2) was produced in the same manner as in Example 1 except that the filaments (1) were changed to (2).

[0147] (Example 3)

[0148] ·Manufacturing of masterbatch

[0149] A masterbatch (3) was obtained in the same manner as in Example 1 except that the setting temperature during the further extrusion processing of polyethylene terephthalate into polypropylene ("Y-2000GV" manufactured by Prime Polymer Co., Ltd.) was changed from 280°C to 230°C.

[0150] ·Filament manufacturing

[0151] 10 parts by mass of the masterbatch (3) was mixed with 100 parts by mass of polypropylene ("Y-2000GV" manufactured by Prime Polymer Co., Ltd.), and then melt-spun at a spinning temperature of 230°C using a spinning machine and stretched 3 times to obtain filaments (3) of 144d / 48F.

[0152] ·Manufacturing of knitted fabrics

[0153] A knitted fabric (3) was produced in the same manner as in Example 1 except that the filaments (1) were changed to (3).

[0154] (Example 4)

[0155] ·Manufacturing of masterbatch

[0156] A masterbatch (4) was obtained in the same manner as in Example 1 except that the set temperature when further extruding polyethylene terephthalate into high-density polyethylene ("SUNTEC HD J320" manufactured by Asahi Kasei Corporation) was changed from 280°C to 160°C.

[0157] ·Filament manufacturing

[0158] 10 parts by mass of the masterbatch (4) was mixed with 100 parts by mass of high-density polyethylene ("SUNTEC HD J320" manufactured by Asahi Kasei Corporation), and then melt-spun at a spinning temperature of 160°C using a spinning machine and stretched 3 times to obtain filaments (4) of 144d / 48F.

[0159] ·Manufacturing of knitted fabrics

[0160] A knitted fabric (4) was produced in the same manner as in Example 1 except that the filaments (1) were changed to (4).

[0161] (Example 5)

[0162] ·Manufacturing of masterbatch

[0163] A masterbatch (5) was obtained in the same manner as in Example 1 except that the set temperature when further extruding polyethylene terephthalate into poly-4-methyl-1-pentene ("TPX DX818" manufactured by Mitsui Chemicals, Inc.) was changed from 280°C to 260°C.

[0164] ·Filament manufacturing

[0165] 10 parts by mass of the masterbatch (5) was mixed with 100 parts by mass of poly-4-methyl-1-pentene ("TPX DX818" manufactured by Mitsui Chemicals, Inc.), and then melt-spun at a spinning temperature of 260°C using a spinning machine, and stretched 3 times to obtain filaments (5) of 144d / 48F.

[0166] ·Manufacturing of knitted fabrics

[0167] A knitted fabric (5) was produced in the same manner as in Example 1 except that the filaments (1) were changed to (5).

[0168] (Example 6)

[0169] ·Manufacturing of masterbatch

[0170] A masterbatch (6) was obtained in the same manner as in Example 1 except that polyethylene terephthalate was changed to polycarbonate ("IUPILON S-3000" manufactured by Mitsubishi Engineering-Plastics Corporation).

[0171] ·Filament manufacturing

[0172] 10 parts by mass of the masterbatch (6) was mixed with 100 parts by mass of polycarbonate ("IUPILON S-3000" manufactured by Mitsubishi Engineering-Plastics Corporation), and the mixture was vacuum dried at 120°C for 12 hours. Then, the mixture was melt-spun at a spinning temperature of 280°C using a spinning machine, and stretched 3 times to obtain filaments (6) of 144d / 48F.

[0173] ·Manufacturing of knitted fabrics

[0174] A knitted fabric (6) was produced in the same manner as in Example 1 except that the filaments (1) were changed to (6).

[0175] (Comparative Example 1)

[0176] ·Manufacturing of metal compound complexes

[0177] A metal compound composite (c1) as a composition containing copper and titanium was obtained in the same manner as in Example 1 except that the particle size adjustment using a horizontal jet mill ("single-pass jet mill" manufactured by Saishin Enterprise Co., Ltd.) and a continuous rotary airflow screening device ("rotary gas sieve" manufactured by Saishin Enterprise Co., Ltd.) was replaced with a pin mill mill ("fine impact mill UPZ" manufactured by Hosokawa Micron Co., Ltd.). The obtained metal compound composite (c1) was observed under an optical microscope (magnification of 200 times) to obtain a particle image, and the particle size (equivalent circle diameter) of at least 1000 particles (primary particles and secondary particles) selected at random was measured, and the maximum particle size was 82 μm.

[0178] The BET specific surface area of ​​the obtained metal compound composite (c1) was 10 m 2 / g.

[0179] ·Manufacturing of masterbatch

[0180] A masterbatch (c1) was obtained in the same manner as in Example 1 except that the metal compound composite (1) was changed to the metal compound composite (c1).

[0181] ·Filament manufacturing

[0182] A filament (c1) was produced in the same manner as in Example 1 except that the masterbatch (1) was changed to the masterbatch (c1).

[0183] ·Manufacturing of knitted fabrics

[0184] The same procedure as in Example 1 was carried out with respect to the filament (c1), thereby producing a knitted fabric (c1).

[0185] (Comparative Example 2)

[0186] ·Manufacturing of masterbatch

[0187] The metal compound complex (1) was replaced with titanium oxide (c2) (photocatalyst titanium oxide "ST-21" manufactured by Ishihara Sangyo Co., Ltd., with a specific surface area of ​​50 m 2 A masterbatch (c2) was obtained in the same manner as in Example 1 except that

[0188] ·Filament manufacturing

[0189] A filament (c2) was obtained in the same manner as in Example 1 except that the masterbatch (1) was changed to the masterbatch (c2).

[0190] ·Manufacturing of knitted fabrics

[0191] The same procedure as in Example 1 was carried out with respect to the filament (c2), thereby producing a knitted fabric (c2).

[0192] (Comparative Example 3)

[0193] ·Manufacturing of masterbatch

[0194] The metal compound composite (1) was replaced with titanium oxide (c3) (titanium oxide "JA-1" manufactured by TAYCA, with a specific surface area of ​​9 m 2 A masterbatch (c3) was obtained in the same manner as in Example 1 except that

[0195] ·Filament manufacturing

[0196] A filament (c3) was obtained in the same manner as in Example 1 except that the masterbatch (1) was changed to the masterbatch (c3).

[0197] ·Manufacturing of knitted fabrics

[0198] The same procedure as in Example 1 was carried out with respect to the filament (c3), thereby producing a knitted fabric (c3).

[0199] (Comparative Example 4)

[0200] ·Filament manufacturing

[0201] A filament (c4) was obtained in the same manner as in Example 1 except that the masterbatch was not used and the amount of the metal compound composite (1) was changed to 3 parts by mass in 100 parts by mass of polyethylene terephthalate "SA-1206".

[0202] That is, 100 parts by mass of polyethylene terephthalate "SA-1206" and 3 parts by mass of the metal compound composite (1) were mixed and melt-kneaded in a φ30 mm twin-screw ventilated extruder (set temperature of 280° C., mesh filter with a particle capture diameter of 40 μm). The obtained thermoplastic resin composition was pelletized. Next, the obtained pellets were vacuum dried at 150° C. for 12 hours, and then melt-spun at a spinning temperature of 290° C. using a spinning machine, and stretched 3 times to obtain filaments (c4) of 144d / 48F (48 strands in a bundle, 144 dtex).

[0203] ·Manufacturing of knitted fabrics

[0204] The same procedure as in Example 1 was carried out with respect to the filament (c4), thereby producing a knitted fabric (c4).

[0205] (Measurement Example 1) Filtration Pressure Measurement (Measurement of Aggregated Particles after Melt Kneading)

[0206] For the obtained masterbatches (1) to (6) and comparative masterbatches (c1) to (c3), a sintered filter with a filter diameter of 25 μm was installed at the front end of the screw of a 25 mm single screw extruder, and the pressure difference when 1 kg of the masterbatch was passed was measured and evaluated according to the following criteria. The results are shown in Table 2.

[0207] ◎Pressure difference is below 1MPa

[0208] ○The pressure difference exceeds 1MPa and is below 5MPa

[0209] △The pressure difference exceeds 5MPa and is below 10MPa

[0210] × Did not pass the filter

[0211] [Table 2]

[0212]

[0213] (Measurement Example 2) Evaluation of Fiber Breakage (Evaluation of Spinnability)

[0214] When spinning the obtained filaments (1) to (6) and the comparative filaments (c1) to (c4), the yarn breakage frequency when processing 1 kg of the raw material was evaluated according to the following criteria. This operation was performed 5 times for the same sample and the average value was set. The results are shown in Table 3.

[0215] ○: Less than 3 times

[0216] △: 3 times or more and less than 10 times

[0217] ×: 10 times or more

[0218] (Measurement Example 3) Measurement of Aggregated Particles in Filaments (Measurement of Aggregates)

[0219] 0.1 g of the obtained filaments (1) to (6) and the filaments (c1) to (c4) for comparative examples were cut and pressed into a film using a microscope specimen. The particle images were obtained by optical microscope observation (magnification 200 times). The particle sizes (equivalent circle diameters) of at least 1,000 particles selected at random (even if they were primary particles, they could also include secondary particles) were measured and evaluated according to the following criteria. The results are shown in Table 3.

[0220] ◎: No more than 1 particle with a size of 20 μm or larger

[0221] ○: There are more than 1 and 5 or less particles larger than 20 μm

[0222] △: The number of particles larger than 20 μm is more than 5 and less than 20

[0223] ×: There are more than 20 particles of 20 μm or larger and at least one particle of 45 μm or larger

[0224] [Table 3]

[0225]

[0226] (Measurement Example 4)

[0227] (Evaluation of antiviral properties in bright places)

[0228] The knitted fabric for evaluation obtained above was subjected to an anti-bacteriophage virus test (refer to JIS R1756).

[0229] 1) Light irradiation conditions: The ultraviolet rays in the light of the white fluorescent lamp were cut off with an N113 filter, and the illumination was set to 1000 lux.

[0230] 2) After dropping 100 μL of a Qβ bacteriophage solution of known concentration on a 5 cm×5 cm evaluation knitted fabric or film, the sample was sandwiched between 5 cm×5 cm glass plates.

[0231] 3) The sample irradiated with light for 4 hours was recovered using SCDLP liquid, and appropriately diluted. The obtained sample was infected with Escherichia coli and spread on agar medium. The number of plaques after culture was counted for evaluation. The antiviral activity was evaluated by the inactivation degree of Qβ phage (the logarithmic value when the relative phage concentration (N / N0) was calculated based on the initial phage concentration N0 and the phage concentration N after a specified time). The inactivation degree of -2 to -5 was evaluated as having antiviral activity. The results are shown in Tables 4 and 5.

[0232] Inactivation degree of -1: 90% inactivation, inactivation degree of -2: 99% inactivation, inactivation degree of -3: 99.9% inactivation, indicating high antiviral activity. Detection limit: inactivation degree of -5.

[0233] ◎: Inactivity is -5.0 or more and less than -4.0

[0234] ○: Inactivity is -4.0 or more and less than -3.0

[0235] △: Inactivity is -3.0 or more and less than -2.0

[0236] ×: Inactivity is -2.0 or more

[0237] (Measurement Example 5)

[0238] (Evaluation of antiviral properties in dark places)

[0239] The same measurement as in "Evaluation of antiviral performance in a bright place" of Measurement Example 4 was performed except that the measurement kit was placed in a dark place and no light was irradiated from a light source. The results are shown in Tables 4 and 5.

[0240] [Table 4]

[0241]

[0242] (Example 7)

[0243] Film manufacturing

[0244] 10 parts by mass of the masterbatch (1) was mixed with 100 parts by mass of polyethylene terephthalate "SA-1206", and then melt-filmed at a film-forming temperature of 280°C using a 20 mm single-screw extruder connected to a 100 mm wide T-die to obtain a 10 μm single-layer film (1).

[0245] (Comparative Example 5)

[0246] Film manufacturing

[0247] 10 parts by mass of the masterbatch (c1) was mixed with 100 parts by mass of polyethylene terephthalate "SA-1206", and then melt-filmed at a film-forming temperature of 280°C using a 20 mm single-screw extruder connected to a 100 mm wide T-die to obtain a 10 μm single-layer film (c1).

[0248] (Measurement Example 6) Evaluation of film processability (measurement of film forming properties)

[0249] The stability during film formation was evaluated. A sintered filter with a filtration diameter of 20 μm was set, and 10 kg of the raw material was used to form a film, and the processability was evaluated. The results are shown in Table 5.

[0250] ○: No pressure increase, film formation completed

[0251] △: Pressure rises, film formation ends

[0252] ×: Film cannot be formed due to increased pressure

[0253] (Measurement Example 7) Measurement of Aggregated Particles in a Thin Film (Measurement of Aggregates)

[0254] 0.1 g of the obtained films (1) and (c1) were cut out and pressed into a film using a microscope specimen, and then observed with an optical microscope (magnification 200 times) to obtain a particle image, and the particle size (equivalent circle diameter) of at least 1,000 particles (primary particles and secondary particles) selected at random was measured, and evaluated according to the criteria of Measurement Example 3. The results are shown in Table 5.

[0255] [Table 5]

[0256] Example 7 Comparative Example 5 Film(No.) 1 c1 Film making properties ○ × Aggregates ○ × Antiviral properties (brightness) ◎ × Antiviral properties (dark) ○ ×

[0257] It is clear that in Examples 1 to 7 in which the metal compound complex was pulverized and classified to remove coarse particles in advance, a masterbatch in which the metal compound complex was highly dispersed can be produced, and further, when processed into a yarn with a small fineness or a thin film, yarn breakage and fracture are not easy to occur, and not only the processability is excellent, but also the antiviral active surface can be exposed to a larger extent on the surface of the molded body by the fine dispersion of the metal compound complex, and the antiviral active effect can be exerted even in a small amount. In contrast, in Comparative Examples 1 and 5 in which the metal compound complex was not pulverized and classified to remove coarse particles in advance, the metal compound complex formed aggregates, and as a result, the pressure difference of the filtration pressure became large, and a masterbatch in which the metal compound complex was highly dispersed could not be produced. As a result, it is clear that when processed into a yarn with a small fineness or a thin film, yarn breakage and fracture are easy to occur, and not only the processability is poor, but also the antiviral active surface cannot be exposed to a larger extent on the surface of the molded body due to the reduced dispersibility of the metal compound complex, and the antiviral active effect cannot be fully exerted.

[0258] (Example 8)

[0259] ·Manufacturing of metal oxides

[0260] 600 parts by mass of a titanium oxide raw material (crystalline rutile type, produced by a sulfuric acid method; BET specific surface area, rutile ratio and primary particle size are shown in Table 6), 8 parts by mass of copper (ii) chloride dihydrate and 900 parts by mass of water were mixed in a stainless steel container.

[0261] [Table 6]

[0262] <![CDATA[BET specific surface area (m 2 / g)]]> 9.0 Rutile rate (mol%) 95.4 Primary particle size (nm) 180

[0263] Next, the mixture is stirred using a stirrer ("ROBOMIX" manufactured by Tokushiki Kagaku Kogyo Co., Ltd.), and a 1 mol / L sodium hydroxide aqueous solution is added dropwise until the pH of the mixed solution reaches 10. Next, the obtained mixed solution is filtered under reduced pressure using a qualitative filter paper (5C), the solid component is separated from the mixed solution, and then, it is washed with ion exchange water. Next, the washed solid matter is dried at 120°C for 12 hours to remove moisture. After drying, a powdered composition is obtained using a mill ("MILCER" manufactured by IWATANI Sangyo Co., Ltd.). Next, using a precision thermostat ("DH650" manufactured by Yamato Scientific Co., Ltd.), the obtained composition is heat treated at 450°C for 3 hours in the presence of oxygen to obtain a powder. The obtained powder is washed with pure water, dried at 80°C, and crushed with the aid of heated gas using a horizontal jet mill (a "single-pass jet mill" manufactured by Saixin Enterprise Co., Ltd.). Thereafter, coarse particles larger than 45 μm are removed using a continuous rotary airflow screening device (a "rotating gas sieve" manufactured by Saixin Enterprise Co., Ltd.), and the maximum particle size is reduced to less than 10 μm using a micro-sieve (with a mesh size of 10 μm), thereby obtaining a metal compound composite (2) which is a composition containing copper and titanium.

[0264] ·Manufacture of aqueous dispersions

[0265] 100 parts by mass of the metal compound composite (2) and 20 parts by mass of a wet dispersant ("DISPERBYK 190" manufactured by BYK-Chemie) were mixed into 280 parts by mass of water as a dispersion medium, and the resulting liquid was dispersed in a bead mill (TSG type manufactured by IMEX) equipped with zirconium oxide beads of the same volume at 1000 revolutions for 4 hours, and the beads were separated by filtration, and then further passed through a filter (mesh size of 1 μm) to obtain an aqueous dispersion (1). The maximum particle size of the metal oxide composite in the obtained aqueous dispersion was 1 μm or less.

[0266] ·Manufacturing of masterbatch

[0267] 100 parts by mass of polyethylene terephthalate ("MA-2101M" manufactured by UNITIKA Corporation, intrinsic viscosity (IV) of 0.63) and 50 parts by mass of aqueous dispersion (1) were pre-mixed to prepare a mixture, and melt-kneaded using a 30 mm φ twin-screw ventilated extruder (set temperature of 280° C.), while evaporating water from the vent. The obtained thermoplastic resin composition was pelletized to obtain a masterbatch (7).

[0268] ·Filament manufacturing

[0269] 10 parts by mass of the masterbatch (7) were mixed with 100 parts by mass of polyethylene terephthalate ("SA-1206" manufactured by UNITIKA, IV: 1.06), and the mixture was dried in vacuo at 150°C for 12 hours. Subsequently, the mixture was melt-spun at a spinning temperature of 290°C using a spinning machine, and stretched 3 times to obtain filaments (7) of 144d / 48F.

[0270] ·Manufacturing of knitted fabrics

[0271] The filaments (7) are false-twisted using a false twisting machine, and a 20-gauge knitted fabric (7) is produced using a circular knitting machine.

[0272] (Example 9)

[0273] ·Manufacturing of masterbatch

[0274] A masterbatch (8) was obtained in the same manner as in Example 8 except that the temperature for further extrusion processing of polyethylene terephthalate into polyamide-6 ("UBE NYLON 1013B" manufactured by Ube Industries, Ltd.) was changed to 260°C.

[0275] ·Filament manufacturing

[0276] 10 parts by mass of the masterbatch (8) was mixed with 100 parts by mass of polyamide-6 modified from polyethylene terephthalate ("UBE NYLON1018" manufactured by Ube Industries, Ltd.), and the mixture was vacuum dried at 110°C for 12 hours. Subsequently, melt spinning was carried out using a spinning machine at a spinning temperature of 260°C, and 144d / 48F filaments (8) were obtained by 3-fold stretching.

[0277] ·Manufacturing of knitted fabrics

[0278] A knitted fabric (8) was produced in the same manner as in Example 8 except that the filaments (7) were changed to (8).

[0279] (Example 10)

[0280] ·Manufacturing of masterbatch

[0281] A masterbatch (9) was obtained in the same manner as in Example 8 except that the temperature for further extrusion processing of polyethylene terephthalate into polypropylene ("Y-2000GV" manufactured by Prime Polymer Co., Ltd.) was changed to 230°C.

[0282] ·Filament manufacturing

[0283] 10 parts by mass of the masterbatch (9) was mixed with 100 parts by mass of polypropylene modified from polyethylene terephthalate ("Y-2000GV" manufactured by Prime Polymer Co., Ltd.), and then melt-spun at a spinning temperature of 230°C using a spinning machine, and stretched 3 times to obtain filaments (9) of 144d / 48F.

[0284] ·Manufacturing of knitted fabrics

[0285] A knitted fabric (9) was produced in the same manner as in Example 8 except that the filaments (7) were changed to (9).

[0286] (Example 11)

[0287] ·Manufacturing of masterbatch

[0288] A masterbatch (10) was obtained in the same manner as in Example 8 except that the temperature for further extrusion processing of polyethylene terephthalate into high-density polyethylene ("SUNTEC HD J320" manufactured by Asahi Kasei Corporation) was changed to 160°C.

[0289] ·Filament manufacturing

[0290] 10 parts by mass of the masterbatch (10) was mixed with 100 parts by mass of high-density polyethylene modified from polyethylene terephthalate ("SUNTEC HDJ320" manufactured by Asahi Kasei Corporation), and then melt-spun at a spinning temperature of 160°C using a spinning machine, and stretched 3 times to obtain filaments (10) of 144d / 48F.

[0291] ·Manufacturing of knitted fabrics

[0292] A knitted fabric (10) was produced in the same manner as in Example 8 except that the filament (7) was changed to (10).

[0293] (Example 12)

[0294] ·Manufacturing of masterbatch

[0295] A masterbatch (11) was obtained in the same manner as in Example 8 except that the temperature for further extrusion processing of polyethylene terephthalate into poly-4-methyl-1-pentene ("TPX DX818" manufactured by Mitsui Chemicals, Inc.) was changed to 260°C.

[0296] ·Filament manufacturing

[0297] 10 parts by mass of the masterbatch (11) is mixed with 100 parts by mass of poly-4-methyl-1-pentene ("TPXDX818" manufactured by Mitsui Chemicals, Inc.) modified from polyethylene terephthalate, and then melt-spun at a spinning temperature of 260°C using a spinning machine, and stretched 3 times to obtain filaments (11) of 144d / 48F.

[0298] ·Manufacturing of knitted fabrics

[0299] A knitted fabric (11) was produced in the same manner as in Example 8 except that the filament (1) was changed to (11).

[0300] (Example 13)

[0301] ·Manufacturing of masterbatch

[0302] A master batch (12) was obtained in the same manner as in Example 8 except that the polyethylene terephthalate was changed to polycarbonate ("IUPILON S-3000" manufactured by Mitsubishi Engineering-Plastics Corporation) and the vacuum drying was performed at 120°C for 12 hours.

[0303] ·Filament manufacturing

[0304] 10 parts by mass of the masterbatch (12) are mixed with 100 parts by mass of polycarbonate modified from polyethylene terephthalate ("IUPILONS-3000" manufactured by Mitsubishi Engineering-Plastics Corporation), and the mixture is vacuum dried at 120°C for 12 hours. Subsequently, melt spinning is carried out using a spinning machine at a spinning temperature of 280°C, and 144d / 48F filaments (12) are obtained by 3-fold stretching.

[0305] ·Manufacturing of knitted fabrics

[0306] A knitted fabric (12) was produced in the same manner as in Example 8 except that the filaments (7) were changed to (12).

[0307] (Example 14)

[0308] ·Manufacture of aqueous dispersions

[0309] 100 parts by mass of the metal compound complex (2) and 40 parts by mass of a wet dispersant ("DISPERBYK 194N" manufactured by BYK-Chemie) are mixed with 280 parts by mass of water as a dispersion medium. The resulting liquid is dispersed in a bead mill (TSG type manufactured by IMEX) equipped with zirconium oxide beads of the same volume at 1000 revolutions for 4 hours. The beads are separated by filtration to obtain an aqueous dispersion (2).

[0310] ·Manufacturing of masterbatch

[0311] 100 parts by mass of polyethylene terephthalate ("MA-2101M" manufactured by UNITIKA Corporation, intrinsic viscosity (IV) of 0.63) and 50 parts by mass of aqueous dispersion (2) were pre-mixed to prepare a mixture, and melt-kneaded using a 30 mm φ twin-screw ventilated extruder (set temperature of 280° C.), while evaporating water from the vent. The obtained thermoplastic resin composition was pelletized to obtain a masterbatch (13).

[0312] ·Filament manufacturing

[0313] 10 parts by mass of the masterbatch (13) were mixed with 100 parts by mass of polyethylene terephthalate ("SA-1206" manufactured by UNITIKA, IV: 1.06), and the mixture was vacuum dried at 150°C for 12 hours. Subsequently, melt spinning was performed using a spinning machine at a spinning temperature of 290°C, and 144d / 48F filaments (13) were obtained by 3-fold stretching.

[0314] ·Manufacturing of knitted fabrics

[0315] The filaments (13) are false-twisted using a false twisting machine, and a 20-gauge knitted fabric (13) is produced using a circular knitting machine.

[0316] (Example 15)

[0317] ·Manufacture of aqueous dispersions

[0318] 100 parts by mass of the metal compound complex (2) and 40 parts by mass of a wet dispersant ("DISPERBYK 2010" manufactured by BYK-Chemie) are mixed with 280 parts by mass of water as a dispersion medium. The resulting liquid is dispersed in a bead mill (TSG type manufactured by IMEX) equipped with zirconium oxide beads of the same volume at 1000 revolutions for 4 hours. The beads are separated by filtration to obtain an aqueous dispersion (3).

[0319] ·Manufacturing of masterbatch

[0320] 100 parts by mass of polyethylene terephthalate ("MA-2101M" manufactured by UNITIKA Corporation, intrinsic viscosity (IV) of 0.63) and 50 parts by mass of aqueous dispersion (3) were pre-mixed to prepare a mixture, and melt-kneaded using a 30 mm φ twin-screw ventilated extruder (set temperature of 280° C.), while evaporating water from the vent. The obtained thermoplastic resin composition was pelletized to obtain a masterbatch (14).

[0321] ·Filament manufacturing

[0322] 10 parts by mass of the masterbatch (14) were mixed with 100 parts by mass of polyethylene terephthalate ("SA-1206" manufactured by UNITIKA, IV: 1.06), and the mixture was vacuum dried at 150°C for 12 hours. Subsequently, melt spinning was performed using a spinning machine at a spinning temperature of 290°C, and 144d / 48F filaments (14) were obtained by 3-fold stretching.

[0323] ·Manufacturing of knitted fabrics

[0324] The filaments (14) are false-twisted using a false twisting machine, and a 20-gauge knitted fabric (14) is produced using a circular knitting machine.

[0325] (Example 16)

[0326] ·Manufacturing of masterbatch

[0327] A masterbatch (15) was obtained in the same manner as in Example 8 except that the temperature for further extrusion processing of polyethylene terephthalate into a low-density polyethylene ("Petrothene 250R" manufactured by Tosoh Corporation) was changed to 140°C.

[0328] Film manufacturing

[0329] 10 parts by mass of the masterbatch (15) was mixed with 100 parts by mass of a low-density polyethylene ("Petrothene 250R" manufactured by Tosoh Corporation), and melt-filmed at a film-forming temperature of 140°C using a 20 mm single-screw extruder connected to a 100 mm wide T-die to obtain a 10 μm single-layer film (2).

[0330] (Example 17)

[0331] Manufacturing of microfibers and nonwovens

[0332] 42 parts by mass of low-density polyethylene ("Petrothene 250R" manufactured by Tosoh Corporation) was mixed with 16 parts by mass of a masterbatch (8) vacuum dried at 105°C for 12 hours and 42 parts by mass of 6-nylon ("UBE NYLON 1013B" manufactured by Ube Industries, Ltd.), and then melt-spun at a spinning temperature of 280°C using a spinning machine, and 220d / 48F filaments (15) were obtained by 3-fold stretching. The obtained filament sample was used to produce an entangled nonwoven fabric through the steps of cutting, carding, cross-lapping and needle punching. The polyethylene was eluted from the obtained entangled nonwoven fabric using toluene, and an entangled nonwoven fabric (1) composed of microfibers having an average fiber diameter of 1 μm was obtained.

[0333] (Example 18)

[0334] ·Manufacturing of multilayer films

[0335] As two types of three-layer films, the surface layer uses 100 parts by mass of low-density polyethylene ("Petrothene 250R" manufactured by Tosoh Corporation) and 10 parts by mass of masterbatch (15), and the middle layer uses 100 parts by mass of low-density polyethylene ("Petrothene 250R" manufactured by Tosoh Corporation). A 300 mm wide T-die is connected, and a main extruder is a 30 mm single-screw extruder and an auxiliary extruder is a 25 mm single-screw extruder. Melt film forming is carried out at a film forming temperature of 140°C to obtain a 30 μm (surface layer / middle layer / surface layer = 2 μm / 20 μm / 2 μm) multilayer film (3).

[0336] (Measurement Example 8) Filtration Pressure Measurement (Measurement of Aggregated Particles after Melt Kneading)

[0337] The obtained master batches (7) to (15) were evaluated in the same manner as in Measurement Example 1. The results are shown in Table 7.

[0338] [Table 7]

[0339]

[0340] (Measurement Example 9) Evaluation of Fiber Breakage (Evaluation of Spinnability)

[0341] The obtained filaments (7) to (14) were evaluated in the same manner as in Measurement Example 2. The results are shown in Table 8.

[0342] (Measurement Example 10) Measurement of Aggregated Particles in Filaments (Measurement of Aggregates)

[0343] The obtained filaments (7) to (14) were evaluated in the same manner as in Measurement Example 3. The results are shown in Table 8.

[0344] [Table 8]

[0345]

[0346] (Measurement Example 11)

[0347] (Evaluation of antiviral properties in bright places)

[0348] The knitted fabrics (7) to (15) for evaluation obtained above were evaluated in the same manner as in Measurement Example 4. The results are shown in Tables 9 and 10.

[0349] (Measurement Example 12)

[0350] (Evaluation of antiviral properties in dark places)

[0351] The knitted fabrics (7) to (15) for evaluation obtained above were evaluated in the same manner as in Measurement Example 5. The results are shown in Tables 9 and 10.

[0352] [Table 9]

[0353]

[0354] (Measurement Example 13) Evaluation of film processability (measurement of film forming properties)

[0355] The stability during film formation was evaluated in the same manner as in Measurement Example 6. The results are shown in Table 9.

[0356] (Measurement Example 14) Measurement of Aggregated Particles in a Thin Film (Measurement of Aggregates)

[0357] The obtained thin films (2) and (3) were evaluated in the same manner as in Measurement Example 7. The results are shown in Table 9.

[0358] [Table 10]

[0359] Example 16 Embodiment 18 Film(No.) 2 3 Film making properties ○ ○ Aggregates ○ ○ Antiviral properties (brightness) ◎ ◎ Antiviral properties (dark) ○ ◎

[0360] (Measurement Example 15) Evaluation of nonwoven fabric (measurement of spinnability)

[0361] The obtained filament (15) was evaluated in the same manner as in Measurement Example 2. The results are shown in Table 11.

[0362] (Measurement Example 16) Measurement of Aggregated Particles in Nonwoven Fabric (Measurement of Aggregates)

[0363] The obtained filament (15) was evaluated in the same manner as in Measurement Example 3. The results are shown in Table 11.

[0364] (Measurement Example 17)

[0365] (Evaluation of antiviral properties in bright places)

[0366] The nonwoven fabric for evaluation (1) obtained above was evaluated in the same manner as in Measurement Example 4. The results are shown in Table 11.

[0367] (Measurement Example 18)

[0368] (Evaluation of antiviral properties in dark places)

[0369] The nonwoven fabric for evaluation (1) obtained above was evaluated in the same manner as in Measurement Example 5. The results are shown in Table 11.

[0370] [Table 11]

[0371] Embodiment 17 Nonwoven fabric(No.) 1 Spinnability ○ Aggregates ○ Antiviral properties (brightness) ◎ Antiviral properties (dark) ◎

[0372] It can be clearly seen that in Examples 8 to 16 obtained by using a metal compound complex obtained from titanium oxide produced by a liquid phase method and further using a masterbatch produced using an aqueous dispersion containing the metal compound complex (b), a masterbatch in which the metal compound complex is highly dispersed can be produced. Furthermore, in Examples 7 to 18, when processed into yarns with a small fineness or into thin films, yarn breakage and fracture are less likely to occur, and not only is the processability excellent, but the antiviral active surface can also be exposed to a greater extent on the surface of the molded body by fine dispersion of the metal compound complex, and the antiviral active effect can be exerted even in a small amount.

Claims

1. A method for producing a resin composition, characterized in that: It has the following steps: Step (1) of preparing a masterbatch by melt-kneading a thermoplastic resin (a) and an aqueous dispersion containing a metal compound complex (b) as necessary raw materials; Step (2) of further melt-kneading the masterbatch obtained in the step (1) with a thermoplastic resin (c), The metal compound composite (b) contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide, and the copper-equivalent content of the divalent copper compound is 0.01 to 20 parts by mass based on 100 parts by mass of the titanium oxide.

2. The method for producing a resin composition according to claim 1, wherein The aqueous dispersion containing the metal compound composite (b) further contains a dispersant.

3. The method for producing a resin composition according to claim 2, wherein The dispersant is an anionic surfactant, a nonionic surfactant, a cationic surfactant or a zwitterionic surfactant.

4. The method for producing a resin composition according to claim 1, wherein The content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more, and the content of the anatase titanium oxide is less than 50 mol %.

5. The method for producing a resin composition according to claim 1, wherein The crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less in the strongest diffraction peak corresponding to the rutile titanium oxide in an X-ray diffraction spectrum obtained by plotting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays.

6. The method for producing a resin composition according to claim 1, wherein In the step (1), the metal compound composite (b) is melt-kneaded in an amount ranging from 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a).

7. The method for producing a resin composition according to claim 1, wherein In the step (2), the thermoplastic resin (c) is melt-kneaded in an amount ranging from 50 to 5000 parts by mass based on 100 parts by mass of the masterbatch.

8. The method for producing a resin composition according to claim 1, wherein The thermoplastic resin (a) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

9. A masterbatch, characterized in that: The invention comprises a thermoplastic resin (a), a metal compound composite (b) and a dispersant, wherein the metal compound composite (b) is contained in an amount in the range of 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a), and the dispersant is contained in an amount in the range of 1 part by mass or more and 100 parts by mass or less relative to 100 parts by mass of the metal compound composite (b). The metal compound composite (b) in the masterbatch contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide, and the copper-equivalent content of the divalent copper compound is 0.01 to 20 parts by mass based on 100 parts by mass of the titanium oxide.

10. The masterbatch according to claim 9, wherein The content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more, and the content of the anatase titanium oxide is less than 50 mol %.

11. The masterbatch according to claim 9, wherein The crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less in the strongest diffraction peak corresponding to the rutile titanium oxide in an X-ray diffraction spectrum obtained by plotting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays.

12. The masterbatch according to claim 9, wherein The thermoplastic resin (a) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

13. A resin composition, characterized in that This is obtained by melt-kneading the thermoplastic resin (c) into the masterbatch according to claim 9.

14. A method for producing a resin composition, characterized in that: The method comprises the step of melt-kneading the thermoplastic resin (c) into the masterbatch according to claim 9. 15 . A molded product obtained by molding the resin composition according to claim 13 .

16. A method for producing a formed body, wherein: The resin composition according to claim 13 is melt-molded.

17. A method for manufacturing a molded product, characterized in that: It has the following steps: Step (1) of preparing a masterbatch by melt-kneading a thermoplastic resin (a) and an aqueous dispersion containing a metal compound complex (b) as necessary raw materials; Step (2) of further melt-kneading a thermoplastic resin (c) into the masterbatch obtained in the step (1); Step (3) of melt-molding the resin composition obtained in step (2), The metal compound composite (b) contains titanium oxide and a divalent copper compound, and has a maximum particle size of less than 45 μm. The specific surface area of ​​the titanium oxide is 3 m 2 / g or more and contains crystalline rutile titanium oxide, and the copper-equivalent content of the divalent copper compound is 0.01 to 20 parts by mass based on 100 parts by mass of the titanium oxide.

18. The method for manufacturing a molded product according to claim 17, wherein: The content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more, and the content of the anatase titanium oxide is less than 50 mol %.

19. The method for manufacturing a molded product according to claim 17, wherein: The crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less in the strongest diffraction peak corresponding to the rutile titanium oxide in an X-ray diffraction spectrum obtained by plotting the diffraction line intensity relative to the diffraction angle 2θ based on Cu-Kα rays.

20. The method for manufacturing a molded product according to claim 17, wherein: In the step (1), the metal compound composite (b) is melt-kneaded in an amount ranging from 10 to 300 parts by mass relative to 100 parts by mass of the thermoplastic resin (a).

21. The method for manufacturing a molded product according to claim 17, wherein: In the step (2), the thermoplastic resin (c) is melt-kneaded in an amount ranging from 50 to 5000 parts by mass based on 100 parts by mass of the masterbatch.

22. The method for manufacturing a molded product according to claim 17, wherein: The thermoplastic resin (a) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

23. The method for manufacturing a molded product according to claim 17, wherein: The thermoplastic resin (c) is at least one selected from the group consisting of polyester, polyamide, polyolefin, thermoplastic elastomer and silicone resin.

24. The method for manufacturing a molded product according to claim 17, wherein: The melt forming in the step (3) is a spinning step or a film and / or sheet forming step.

Citation Information

Patent Citations

  • Burotsukunoyojooyobiparetsutonoridatsuhohotosonosochi

    JP1978043176B2

  • Resin composition for fiber processing and fabric using the same

    JP2017155368A